International labor migration: features of the Eurasian model - Khamzin, A.Sh.; Shakenov, A.O.; Boretskiy, A.V. (Bulletin of the Karaganda University “Law Series”, 2021)
The authors of the article consider the issues of the current state and prospects for improving the regulatory framework of the Eurasian Economic Union and the legislation of the Republic of Kazakhstan in the context of further development of the legal framework for cooperation in the field of labor migration, as well as in the field of integration and migration policy of the countries of the Eurasian Economic Union and the Republic of Kazakhstan. The purpose of the study is to develop proposals for improving the regulatory framework of the EAEU countries and the legislation of the Republic of Kazakhstan in the field of regulation of labor migration, as well as countering its negative consequences such as illegal migration on the territory of this integrational association.The methodological basis of the research consists of traditional general scientific and special legal methods used in comparative law: system-structural, historical-legal, socio-legal and comparative-legal. The authors conclude that it is necessary to develop and adopt the Law "On Labor Migration" in the Republic of Kazakhstan, which will be aimed at regulating both the departure of citizens of the Republic of Kazakhstan for employment abroad and the attraction of foreign labor to the Republic of Kazakhstan, with all the legal relations arising from these processes. The results of this study will contribute to improve the regulatory framework in the field of legal regulation of labor migration, countering illegal migration and other illegal manifestations, which are largely the result of insufficient regulation of the sphere of labor migration